Comparison of Atypical and Osteoporotic Femoral Shaft Fractures in the Elderly: A Multicenter Study - Takanori Miura; Hiroaki Kijima; Noriyuki Ishikawa; Toshihito Ebina; Takayuki Tani; Shuichi Chida; Tetsuya Suzuki; Satoshi Yumto; Hiroshi Tazawa; Naohisa Miyakoshi; Yoichi Shimada (Advances in Orthopedics)
Background. In atypical femoral fractures, owing to the high rates of complications and delayed healing that accompany the plate fixation, the most favorable treatment is intramedullary nailing. Although there is insufficient evidence, plate fixation is chosen due to anterolateral bowing of the femur. This study compared the bone healing time and rates of complications in atypical femoral shaft fractures and osteoporotic femoral shaft fractures. Methods. We searched the medical records of 3 institutions in Japan for patients with femoral shaft fractures who visited between 1 January 2010 and 31 December 2015. We identified 65 patients and excluded 37 among these due to high-energy injuries or being younger than 65 years. Among the remaining patients, we identified 17 and 11 women with atypical (AFF group) and osteoporotic femoral shaft fractures (OP group), respectively. Results. In surgical method, there were differences in intramedullary nailing (94.1% versus 27.2%) (p<0.01). The mean bone healing time was 11.1 months versus 6.7 months in 2 groups (p<0.01). Iatrogenic femoral fractures during intramedullary nail insertion were observed in both groups, and reoperation was only seen in atypical femoral fractures treated with a plate fixation, but there was no difference in the rate of complications (23.5% versus 9.1%). Conclusions. In the atypical femoral fracture group, intramedullary nailing was more chosen, but the bone healing time was delayed and plate fixation cases needed reoperation. There was no significant difference in the rate of complications between the 2 groups.